2015
DOI: 10.2337/dc14-2890
|View full text |Cite
|
Sign up to set email alerts
|

High Rate of Spontaneous Normalization of Celiac Serology in a Cohort of 446 Children With Type 1 Diabetes: A Prospective Study

Abstract: OBJECTIVEIn children with type 1 diabetes mellitus (T1DM), elevated levels of antitissue transglutaminase (anti-tTG) antibody may spontaneously normalize, despite continued consumption of gluten. We aimed to investigate the prevalence of spontaneous normalization of anti-tTG levels and the existence of factors predictive for this outcome. RESEARCH DESIGN AND METHODSAll children referred from 2002 to 2012 were screened for celiac disease (CD) at diabetes onset and at specific intervals. In the presence of a hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
47
2
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(71 citation statements)
references
References 33 publications
8
47
2
4
Order By: Relevance
“…However, the authors confirmed that all these subjects had a weak EmA reactivity. In the study by Castellaneta et al (1), the median time for tTG normalization was shorter than in our study, 1.3 years. We think it is unlikely that EmA can have a longer time for normalization than tTG, as the authors affirmed that they did not find any cases that were both EmA positive and tTG negative.…”
contrasting
confidence: 74%
See 1 more Smart Citation
“…However, the authors confirmed that all these subjects had a weak EmA reactivity. In the study by Castellaneta et al (1), the median time for tTG normalization was shorter than in our study, 1.3 years. We think it is unlikely that EmA can have a longer time for normalization than tTG, as the authors affirmed that they did not find any cases that were both EmA positive and tTG negative.…”
contrasting
confidence: 74%
“…We read with interest the data reported by Castellaneta et al (1) about the spontaneous normalization of autoantibody markers for celiac disease (CD) in a wide population of children and adolescents with type 1 diabetes mellitus (T1DM). The authors hypothesized that this phenomenon could be related to a state of temporary positivity of celiac serology in children with T1DM.…”
mentioning
confidence: 99%
“…Such transient autoantibodies may limit public acceptance of universal screening[15][38]. Others have also observed fluctuating tTGA[15] and transient tTGA antibodies in children with serial testing[3941]. Continued long term follow-up will identify whether the autoimmunity in these subjects truly abates and tolerance develops, or if CDA will recur in time, possibly in response to additional stimulating events.…”
Section: Discussionmentioning
confidence: 99%
“…7,87 Spontaneous positive to negative sero conversion has been observed, which indicates that, at least in children, coeliac autoimmunity might be tran sient. [88][89][90] However, the same phenomenon occurs very rarely in adults. As coeliac disease remains undiagnosed in 60-80% of cases and 1-2% of individuals are at risk of coeliac disease, screening tools that do not depend on the patient's clinical presentation are needed.…”
Section: Disease Managementmentioning
confidence: 83%